Proceedings of the 2011 15th International Conference on Computer Supported Cooperative Work in Design (CSCWD) 2011
DOI: 10.1109/cscwd.2011.5960057
|View full text |Cite
|
Sign up to set email alerts
|

Resilient workflows for cooperative design

Abstract: This paper describes an approach to extend process modeling for engineering design applications with fault-tolerance and resilience capabilities. It is based on the requirements for application-level error handling, which is a requirement for petascale and exascale scientific computing. This complements the traditional fault-tolerance management features provided by the existing hardware and distributed systems. These are often based on data and operations duplication and migration, and on checkpoint-restart p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The Disaster Simulation system [29] assesses the evolution and impact of various physical phenomena, in domains such nuclear and environmental science. Aircraft industries use large scale multi-physics applications (aircraft flight dynamics simulation) to reduce the time of development [30]. The Ensemble Kalman Filter (EnKF) method is an important application in the petroleum industry for reservoir and groundwater modelling, and is used for operational monitoring and prediction [31].…”
Section: Discussionmentioning
confidence: 99%
“…The Disaster Simulation system [29] assesses the evolution and impact of various physical phenomena, in domains such nuclear and environmental science. Aircraft industries use large scale multi-physics applications (aircraft flight dynamics simulation) to reduce the time of development [30]. The Ensemble Kalman Filter (EnKF) method is an important application in the petroleum industry for reservoir and groundwater modelling, and is used for operational monitoring and prediction [31].…”
Section: Discussionmentioning
confidence: 99%
“…They can involve complex processing, possibly requiring data to go sequentially through a series of different software, possibly taking days to compute. To minimize the risk of failure, it has been suggested that workflows should be broken down in smaller steps and use checkpoints systems (Gross et al 2008;Nguyên, Trifan, and Désidéri 2011). In some cases, workflows can be saved as templates, exported, and shared for reuse (Bergmann, Demuth, and Sander 2011).…”
Section: How Is Scientific Software Developed and Used?mentioning
confidence: 99%